دينامية العلامة في العرض المسرحي ، من ما وراء النص إلى ما خلف الستار - بغدادي, نسيمة (Université de M'sila, 2017)
This paper aims at showing the studies which consider the theatrical by the show that celebrates this --- -- - -ssociation between negatively the concept of theatrical sign. In this perspective, this research paper highlights the theatrical sign dynamism, its semantic and semiotic density that result from the show which consists of performance, usic, lighting, decors, actors, body language…etc.
Keywords: Symiology; theatrical